2015
DOI: 10.1124/dmd.114.062034
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Expression of Hepatic Organic Anion–Transporting Polypeptide (OATP) Transporters in Cellular Systems Relative to Human Liver Tissue

Abstract: Organic anion-transporting polypeptide (OATP)1B1, OATP1B3, and OATP2B1 transporters play an important role in hepatic drug disposition. Recently, an increasing number of studies have reported proteomic expression data for OATP transporters. However, systematic analysis and understanding of the actual differences in OATP expression between liver tissue and commonly used cellular systems is lacking. In the current study, meta-analysis was performed to assess the protein expression of OATP transporters reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 41 publications
3
61
1
Order By: Relevance
“…Although there is no clear guidance on the uptake rate required, the initial screen and selection of the hepatocyte lot is critical for success. The expression level of OATP1B1 and OATP1B3 (18.3 and 1.7 fmol/million cells) in the hepatocyte lot used in the study is within the range of the literature reported level (3.4–23.2 for OATP1B1 and 1.5–6.5 for OATP1B3) 27, 28, 29, 30. Because pravastatin undergoes only minimal metabolism and the incubation time was short, metabolism in hepatocyte is likely not an issue in this study.…”
Section: Discussionsupporting
confidence: 78%
“…Although there is no clear guidance on the uptake rate required, the initial screen and selection of the hepatocyte lot is critical for success. The expression level of OATP1B1 and OATP1B3 (18.3 and 1.7 fmol/million cells) in the hepatocyte lot used in the study is within the range of the literature reported level (3.4–23.2 for OATP1B1 and 1.5–6.5 for OATP1B3) 27, 28, 29, 30. Because pravastatin undergoes only minimal metabolism and the incubation time was short, metabolism in hepatocyte is likely not an issue in this study.…”
Section: Discussionsupporting
confidence: 78%
“…Particularly, with recent advances in proteomic methods, robust analyses of the protein expression patterns of UGT enzymes in different tissues and in vitro systems Fallon et al, 2013b) made it possible to derive reliable relative expression factors (REFs) essential to these drug-related simulation exercises (Knights et al, 2016). More recent reports have, however, highlighted significant levels of interlaboratory discrepancy between abundance measurements of drugmetabolizing enzymes and drug transporters (Achour et al, 2014c;Badée et al, 2015), even when matched samples were analyzed (Harwood et al, 2016a), necessitating further investigations into the factors contributing to these discrepancies. To illustrate this point, the present study reports comparative analysis of a set of eight UGT enzymes quantified by two distinct proteomic methodologies (SIL and QconCAT-based approaches) in matching samples, with correlation of these abundances against rates of glucuronidation for seven UGT substrates, highlighting large interlaboratory discrepancies between the reported protein levels of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the abundance of hepatic organic anion transporting polypeptide 1B1 showed a wide variation (up to 10-fold) in sets of nonmatched samples measured using two different methodological workflows Vildhede et al, 2014). Meta-analyses of abundance measurements of drug-metabolizing P450 enzymes (Achour et al, 2014b), UGT enzymes (Achour et al, 2014c), and drug transporters (Badée et al, 2015) revealed up to 600-, 250-, and 100-fold differences in collated data, respectively, with a large level of interstudy heterogeneity (Higgins and Thompson's index of up to 99%), suggesting that variability in data used in pharmacokinetic extrapolation and simulation cannot be attributed to biologic interindividual variation in expression alone.…”
Section: Introductionmentioning
confidence: 99%
“…(3,37,46); the overall trends suggest substantial inter-individual variabilities in the expression of drug transporters, consistent with limited available functional activity data (37). Quantitative proteomic transporter abundance data are available for human organs such as intestine, liver and brain (95)(96)(97), as well as rat kidney (98). Data for human kidney have recently been published; of the solute carrier transporters (SLC), MATE1 and OAT3 were the most abundant (10.8 and 9.7 pmol/mg microsomal protein, respectively), whereas Pgp/MDR1 was the most abundant ATP-binding cassette (ABC) transporter (4.45 pmol/mg microsomal protein) (22).…”
Section: Amount Of Specific Drug Transporters In Kidneymentioning
confidence: 99%
“…Although data are available concerning renal developmental patterns of transporters in rodent species, minimal expression data are available for human (99). LC-MS/MS methods are currently favoured for measuring transporter abundance in tissue homogenates and subcellular fractions due to the high precision and ability to assess inter-individual and inter-study variability in transporter expression (96). Complimentary technologies such as matrix-assisted laser desorption/ionisation (MALDI)-imaging mass spectrometry, secondary ion mass spectrometry and flow cytometry (100, 101) may allow quantitative analysis of transporter localisation at the tissue and/or subcellular scales (e.g.…”
Section: Amount Of Specific Drug Transporters In Kidneymentioning
confidence: 99%